Efektivitas Metode Problem-Based Learning dalam Pembelajaran Mata Kuliah Teori Psikologi Kepribadian II - Supratiknya, -; Kristiyani, Titik (Jurnal Psikologi, 2006)
This study aims at uncovering: (1) whether the problem-based learning (PBL) method is effective to teach a theoretical subject such as Personality Psychology II; (2) how effective is the PBL method compared to the traditional method to teach a theoretical subject such as Personality Psychology II; and (3) whether the teacher factors affect the effectiveness of the PBL method to teach a theroretical subject such as Personality Psychology II. Three available classes of Subjects enrolling in Personality Psychology II, two of which were taught with the PBL method by a senior-male-demanding teacher and a junior-female-easy-going teacher respectively while the other one was taught with the traditional method by the senior-male-demanding teacher, participated in the study. Designed as a quasi-experimental research, the results showed that the first two aims of the study were confirmed. Regarding the teacher factors effect, the study showed a direct and positive relation between the Subjects’ number of study hour and their achievement disregarding both the teaching method and the teacher factors as well as a complicated relation between the Subjects’ learning satisfaction and their achievement presu¬mably involving both the teaching method and the teacher factors with the various aspects of teacher competencies. A further study on the last matter seems to be needed. Keywords: problem-based learning, out¬come-oriented assessment, pro¬cess-oriented self-directed learn¬ing, independent learning.